PENGARUH PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA ASN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA RSUD BESUKI KABUPATEN SITUBONDO - Marharani, Dyajeng; Arief, Muhammad Yahya; Pramesthi, Riska Ayu (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Factors that affect performance apart from being competent in their field or according to competence, one of which is work discipline, as well as education and training. Work discipline is a form of training that seeks to improve and shape the knowledge, attitudes and behavior of employees to try to work cooperatively. Education and training have a very significant impact on the achievement of organizational goals. The purpose of this study was to analyze and examine the effect of Education and Training on Performance through Work Discipline as an Intervening Variable at Besuki Hospital, Situbondo Regency. The population in this study were ASN employees (other than organizational leaders) Besuki Hospital, Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model – Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that Education and Training has a significant positive effect on work discipline, Education and Training has a significant positive effect on Performance, Work discipline has a significant positive effect on Performance, Education and Training has a significantly positive effect on Performance through Discipline work.